Analysis of Mathematical Communication Skills Vocational School Students Assisted Desmos in Solving Mathematics of Finance - Ramadhan, Sahrul; Setyaningrum, Wahyu (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
One of the mathematical skills that students must have been mathematical communication skills. Mathematical communication skills enable students to convey their understanding of mathematical concepts. The process of expressing mathematical ideas verbally or in writing helps students understand the material more deeply. Other previous research only described the effectiveness of software on mathematical communication skills, this study aims to analyze students' mathematical communication skills in 21st century learning when solving financial math problems with the help of desmos. This research is descriptive research with a qualitative approach. The results showed that the mathematical communication skills of class 11 SIJA B of 12 students belonged to the medium category. Desmos media has the potential to improve students' mathematical communication skills. A total of 2 students in the high mathematical communication skills category with a percentage of 16.7% were able to master all indicators of mathematical communication skills, 8 students in the moderate mathematical communication skills category with a percentage of 66.6% and some students were able to master all indicators of mathematical communication skills but were still lacking perfect, and 2 students in the low mathematical communication skills category with a percentage of 16.7% were only able to master one indicator, namely the second indicator of mathematical communication skills. The implications of this research are to investigate effective teaching methods to improve students' mathematical communication skills. Integrate tasks and activities that encourage mathematical communication in learning materials and further explore how technology can be applied to improve mathematical communication skills. Salah satu keterampilan matematika yang harus dimiliki peserta didik adalah kemampuan komunikasi matematis. Ketrampilan komunikasi matematis memungkinkan siswa untuk menyampaikan pemahaman mereka tentang konsep matematika. Proses mengungkapkan ide-ide matematis secara verbal atau tertulis membantu siswa memahami materi dengan lebih mendalam.  Penelitian lain sebelumnya hanya mendeskripsikan keefektifan software terhadap kemampuan komunikasi matematis, penelitian ini bertujuan menganalisis kemampuan komunikasi matematis siswa dalam pembelajaran abad-21 saat menyelesaikan soal matematika keuangan berbantuan desmos. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa kemampuan komunikasi matematis kelas 11 SIJA B dari 12 peserta didik tergolong pada kategori sedang. Media desmos berpotensi untuk meningkatkan kemampuan komunikasi matematis peserta didik. Sebanyak 2 siswa pada kategori kemampuan komunikasi matematis tinggi dengan persentase 16,7% mampu menguasai semua indikator kemampuan komunikasi matematis, 8 siswa pada kategori kemampuan komunikasi matematis sedang dengan persentase 66,6% dan beberapa siswa mampu menguasai semua indikator kemampuan komunikasi matematis namun masih kurang sempurna, dan 2 siswa pada kategori kemampuan komunikasi matematis rendah dengan persentase 16,7% hanya mampu menguasai satu indikator , yaitu indikator kedua dari kemampuan komunikasi matematis. Implikasi penelitian ini agar menyelidiki metode pengajaran yang efektif untuk meningkatkan ketrampilan komunikasi matematis siswa. Mengintegrasikan tugas dan aktivitas yang mendorong komunikasi matematis dalam materi pembelajaran dan lebih mengeksplorasi bagaimana teknologi dapat diterapkan untuk meningkatkan ketrampilan komunikasi matematis.